Diagnosis and Management of Iron Deficiency Anaemia in Children — A Clinical Update - Elaine Chu Shan Chew MRCPCH, MMED (Proceedings of Singapore Healthcare, 2012)
Iron deficiency anaemia (IDA) remains an important public health problem even in developed countries like Singapore. This clinical update covers recent developments in the knowledge of iron metabolism, which aids in the approach towards the diagnosis, management and prevention of IDA in children. Besides IDA, iron deficiency (ID) has several non-haematological consequences including effects on neurocognition and immune function as suggested by several animal and clinical studies. Thus paediatricians and other health care providers should work towards the prevention and elimination of IDA in children.